2021
DOI: 10.1017/s0266466621000207
|View full text |Cite
|
Sign up to set email alerts
|

Constraint Qualifications in Partial Identification

Abstract: The literature on stochastic programming typically restricts attention to problems that fulfill constraint qualifications. The literature on estimation and inference under partial identification frequently restricts the geometry of identified sets with diverse high-level assumptions. These superficially appear to be different approaches to closely related problems. We extensively analyze their relation. Among other things, we show that for partial identification through pure moment inequalities, numerous assum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It is worth highlighting that Assumption 4 places restrictions on the variance of Y n,0 but not on its mean µ n,0 . This contrasts with linear independence constraint qualification (LICQ) assumptions that have been considered in other work (e.g., Cho & Russell 2021, Gafarov 2019, which restrict the set of moments that can be binding in population and thus the value of µ n,0 (see Kaido et al (2021) for discussion). In the simplest case without nuisance parameters (X n,0 =0), for example, Assumption 4 holds if all of the elements of Y n,0 have positive variance and are not perfectly correlated, whereas a standard LICQ condition would impose that µ n,0 has a unique maximum element.…”
Section: Structure Of the Formmentioning
confidence: 97%
See 1 more Smart Citation
“…It is worth highlighting that Assumption 4 places restrictions on the variance of Y n,0 but not on its mean µ n,0 . This contrasts with linear independence constraint qualification (LICQ) assumptions that have been considered in other work (e.g., Cho & Russell 2021, Gafarov 2019, which restrict the set of moments that can be binding in population and thus the value of µ n,0 (see Kaido et al (2021) for discussion). In the simplest case without nuisance parameters (X n,0 =0), for example, Assumption 4 holds if all of the elements of Y n,0 have positive variance and are not perfectly correlated, whereas a standard LICQ condition would impose that µ n,0 has a unique maximum element.…”
Section: Structure Of the Formmentioning
confidence: 97%
“…We now briefly discuss the connections and differences between Assumption 4 and linear independence constraint qualification (LICQ) conditions that have been imposed in the literature. We refer the reader to Kaido et al (2021) for detailed discussion of constraint qualifications in the moment inequality literature, and Appendix A.2 of Rambachan & Roth (2021) for additional results for our conditional test under LICQ.…”
Section: Starting From {Nmentioning
confidence: 99%
“…It is worth highlighting that Assumption 4 involves the variance of Y n,0 but not its mean µ n,0 . This contrasts with linear independence constraint qualification (LICQ) assumptions that have been considered in other work (e.g., Cho & Russell 2021, Gafarov 2019), which restrict the set of moments that can bind in population and thus the value of µ n,0 (see Kaido et al (2021) for discussion). In the simplest case without nuisance parameters (X n,0 = 0), for example, Assumption 4 holds if all of the elements of Y n,0 have positive variance and are not perfectly correlated, whereas a standard LICQ condition would impose that µ n,0 has a unique maximum element.…”
Section: Let ⌥mentioning
confidence: 99%
“…We now briefly discuss the connections and differences between Assumption 4 and linear independence constraint qualification (LICQ) conditions that have been imposed in the literature. We refer the reader to Kaido et al (2021) for detailed discussion of constraint qualifications in the moment inequality literature, and Section 3 of Rambachan & Roth (2022) for additional results for our conditional test under LICQ.…”
mentioning
confidence: 99%
“…(2) The assumption on λ ∈ Λ is a type of Mangasarian-Fromowitz constraint qualification. See Kaido et al (2022) for a discussion of constraint qualifications in partially identified models.…”
Section: Parameter On the Boundarymentioning
confidence: 99%